Behavior Problems in Four-Year-Old Children from a Brazilian Birth Cohort - Cruz, Suélen Henriques (2022)
This study aimed to investigate the occurrence of behavior problems in 3750 four years old children from a birth cohort. Children were followed from birth to four years old through home visits, and questionnaires on child health and development and the Child Behavior Checklist 4-18/CBCL were applied. Prevalence rates were high (total problems 35.6%), particularly externalizing problems, which occurred in 44.4 % of children (48.3% girls; 40.6% boys; p < 0.001). Internalizing problems were less prevalent, occurring in 15.5 % of children (19.1% boys; 11.6% girls; p < 0.001). Regardless of sex, there was a higher prevalence of behavioral problems in children with younger siblings, whose mothers had less education and had no partner.